Tembikar Pada Gua Kuya di Desa Pondoa Kecamatan Wiwirano Kabupaten Konawe Utara Provinsi Sulawesi Tenggara (Kajian Bentuk dan Ragam Hias) - yanirsa abigael; abdul Rauf Sulaeman (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2017)
This study examines the shape and variety of pottery fragments found in Kuya Cave in Pondoa Village, Wiwirano District, Konawe Utara District, Southeast Sulawesi Province. There are 3 analytical methods used in this study, namely (1) Morphological Analyst,(2) Stilistic Analysis(Ornamental Variety), (3) Technology Analysis (Engineering). The number of samples used in this study is 46. Of these there are 14 pottery fragments that can be reconstructed 7 of which are in theform of bowls, 6 of which are potsand 1 jar. In addition, there are 2 handrails and 2 parts in the form of carcass fragments. The remaining 14 are in the form of body fragments with various forms of decoration. Based on the analysis of ornamentation carried out on this pottery there are 7 decorative types, namely lines, circles, triangles, rectangles, meanders, points and rhombus. Whilethe application of decorative techniques there are 4 techniques, namely scratch technique, press technique, paste technique and puncture technique. Based on the results of the study, Kuya Cavepottery has the same characteristics as the old traditional pottery namely Sa Huynh Kalanay pottery. This equation can be seen from the shape, decoration and application of decorative techniques on each pottery.